Compassionate use of delamanid in combination with bedaquiline for the treatment of multidrug-resistant tuberculosis. Issue 1 (10th January 2019) - Hafkin, Jeffrey; Hittel, Norbert; Martin, Alexandra; Gupta, Rajesh
Patients with multidrug-resistant (MDR) tuberculosis (TB), in particular those with pre-extensively drug-resistant (pre-XDR) and extensively drug-resistant (XDR)-TB, and those that fail standard second-line therapy, are difficult to treat and have poor long-term outcomes [1]. To address this unmet medical need, there is strong interest in exploring the combined use of delamanid and bedaquiline, the only two anti-TB drugs approved for the treatment of pulmonary MDR-TB in the last 40 years, as their novel mechanisms of action may offer treatment alternatives for patients who have developed resistance or non-tolerability to existing anti-TB drugs [2, 3]. Despite the initial regulatory approvals of bedaquiline and delamanid in 2012 and 2014, respectively, global usage of both drugs in combination with one another remains limited in part due to the uncertainty around the safety and efficacy of such a combination regimen. Hence, there is an urgent need for programmatic data to better understand the "real-world" use of these two medicines used together in MDR-TB patients. Updated data from the Otsuka compassionate use programme show that regimens combining delamanid and bedaquiline appear effective in MDR-TB cases with limited treatment options http://ow.ly/zdE330mlkLN